2021
DOI: 10.1029/2019ja027285
|View full text |Cite
|
Sign up to set email alerts
|

Cloud Formation From a Localized Water Release in the Upper Mesosphere: Indication of Rapid Cooling

Abstract: Polar mesospheric clouds (PMCs) occur in the summer near 82 ‐85km altitude due to seasonal changes of temperature and humidity. However, water vapor and associated PMCs have also been observed associated with rocket exhaust. The effects of this rocket exhaust on the temperature of the upper mesosphere are not well understood. To investigate these effects, 220 kg of pure water was explosively released at 85 km as part of the Super Soaker sounding rocket experiment on the night of January 25–26, 2018 at Poker Fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…The monthly average cloud frequencies presented here are also quite low (<1%, see Figure 4), so they can be more affected by water‐rich exhaust plumes from lower latitudes. Furthermore, recent work has shown that the plume water vapor itself with its extremely high concentrations can locally cool the upper mesosphere to enable cloud formation, even in the polar winter (Collins et al., 2021).…”
Section: A Case Study Of Space Traffic Exhaust Forming Mid‐latitude M...mentioning
confidence: 99%
See 1 more Smart Citation
“…The monthly average cloud frequencies presented here are also quite low (<1%, see Figure 4), so they can be more affected by water‐rich exhaust plumes from lower latitudes. Furthermore, recent work has shown that the plume water vapor itself with its extremely high concentrations can locally cool the upper mesosphere to enable cloud formation, even in the polar winter (Collins et al., 2021).…”
Section: A Case Study Of Space Traffic Exhaust Forming Mid‐latitude M...mentioning
confidence: 99%
“…Figure 8 does not consider size of launch vehicle (e.g., Stevens et al., 2012), launch site latitude (Table 2), ascent trajectory, or the water vapor yield of the propellant combination which requires additional study that is beyond the scope of this work. On the other hand it should be emphasized that water vapor mixing ratios from a single plume can be near unity (e.g., Collins et al., 2021 and references therein) and are many orders of magnitude larger than ambient mixing ratios, which are typically reported in parts per million at these altitudes. Figures 8a and 8b provide evidence that the migrating tides (i.e., those that follow the sun) contribute importantly to the northward transport of space traffic exhaust during the summer.…”
Section: Mid‐latitude Mesospheric Clouds and The Launch Recordmentioning
confidence: 99%
“…(2007), DeLand and Thomas (2019), and Shettle et al. (2009) reported an increase in the occurrence, frequency, and brightness of polar mesospheric clouds (PMCs), themselves a sensitive indicator of climate change as they occur under specific conditions of both temperature and water vapor content (Collins et al., 2021). The predicted temperature changes in the middle atmosphere (up to 2–3 K dec −1 cooling) are much larger than the warming at the surface (∼0.5 K dec −1 during the last 50 years (IPCC, 2021)), indicating that the middle and upper atmosphere are very sensitive and could act as an early warning signal for future climate change.…”
Section: Introductionmentioning
confidence: 99%
“…Transport over the Atlantic resulted in observed increases in water vapor in the sub‐Arctic and in PMC brightness in the Arctic (Stevens et al., 2012 ). More recently, an experiment depositing water vapor in the mesosphere showed the vapor locally cooled and increased the frost point, leading to the rapid formation of PMCs (Collins et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%